Maps telling stories? - Mocnik, Franz-Benjamin; Fairbairn, David (The cartographic journal, 2018)
Maps are good at representing geographic space, but texts have a stronger affordance of telling a story than maps. Telling stories is, however, important to make information more personal and to arrest the map user's attention. This paper contrasts the map and the text media in order to understand why texts are good at telling a story but conventional maps are not. We demonstrate that, by a modification of maps, appropriate structural features of the text media can be transferred to maps, which makes them more suitable for telling stories. This new concept for map design can lead to new interaction possibilities and provide insights into how maps can be used more effectively.